Nyeri Kala I Fase Aktif Persalinan Pada Ibu Inpartu Terhadap Pengaruh Endorphine Massage di RSUD Mamuju - Thalib, Kiki Uniatri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2022)
Childbirth is the process of expelling the products of conception (fetus and uri) that are full term or can live outside the womb through the birth canal or through other means with or without assistance. Endorphin Massage has a positive impact, namely that it can manage pain, help provide a sense of calm and comfort, before or during the birth process and the results obtained have a significant influence between variables. The aim of this study was to find out the effect of endorphin massage on pain during the first stage of the active phase of labor in postpartum mothers at RSUD. The method used is Quasy Experiment with a Nonequivalent Control Group Design, which is a type of research that observes population or sample data only once at the same time. The population in this study were all women giving birth normally and the samples in this study were some of the women giving birth who were in RSUD as many as 30 people, of which 15 people were given Endorphine massage and 15 people were not given Endorphine massage. The sampling for this study was carried out by Purposive Sampling and using Independent Sample T Test. The results of the study showed that there was an effect of endorphin massage on pain during the first stage of the active phase of labor in postpartum mothers at RSUD.